Earthquake Detection and Tsunami Disaster Management Using Vibration Sensors - Jihan Nadirah Simatupang; Fauziah; Fitri Ramadhani Pane; M. Irfan Affandi; Roberto Kaban; Surizar Rahmi Danur (JCEIT: Journal of Computer Engineering and Information Technology, 2025)
An earthquake is a vibration or tremor that occurs on the Earth's surface due to a sudden release of energy from within that creates seismic waves. The frequency of an area refers to the type and size of earthquakes experienced over a period of time. Along with the development of earthquake detection system technology provides a solution to minimize the impact of earthquake events. Natural disasters that often occur in the country of Indonesia, one of the natural disasters that often occur is earthquakes. And many people do not know when an earthquake will come.  So an earthquake detection tool was made with Arduino Uno which is a tool that can detect earthquake vibrations. With this tool using a vibration sensor sensor that can detect vibrations. REFERENCES Agustanti, Sri Primaini, Hartini Hartini, Nurhayani Nurhayani, and Dimas Dibya Hartanto. 2022. “Aplikasi Mikrokontroler Arduino Uno Dalam Rancang Bangun Kunci Pintu Menggunakan E-Ktp.” Jusikom : Jurnal Sistem Komputer Musirawas 7(1):74–88. doi: 10.32767/jusikom.v7i1.1611. Al-Ali, A. R., Beheiry, S., Alnabulsi, A., Obaid, S., Mansoor, N., Odeh, N., & Mostafa, A. (2024). An IoT-Based Road Bridge Health Monitoring and Warning System. Sensors, 24(2), 469. https://doi.org/10.3390/s24020469 Ayuningtyas, D., Windiarti, S., Hadi, M. S., Fasrini, U. U., & Barinda, S. (2021). Disaster Preparedness and Mitigation in Indonesia: A Narrative Review. Iranian Journal of Public Health. https://doi.org/10.18502/ijph.v50i8.6799 Basid, A., Mahardika, I. K., Subchan, W., & Astutik, S. (2021a). Mapping risk levels of earthquake damage as disaster mitigation efforts: Case studies in West Java, Central Sulawesi and Lombok. 040007. https://doi.org/10.1063/5.0037540 Chen, H., Li, G., Fang, R., & Zheng, M. (2021). Early Warning Indicators of Landslides Based on Deep Displacements: Applications on Jinping Landslide and Wendong Landslide, China. Frontiers in Earth Science, 9, 747379. https://doi.org/10.3389/feart.2021.747379 Clements, T. (2023). Earthquake Detection with tinyML. Seismological Research Letters. https://doi.org/10.1785/0220220322 Dhira, Y., Meilano, I., & Dudy, D. W. (2021). Analysis of Tectonic Plate Velocity Variations in the Sunda Strait Based on GPS Time-series Data. IOP Conference Series: Earth and Environmental Science, 873(1), 012084. https://doi.org/10.1088/1755-1315/873/1/012084 Esposito, M., Palma, L., Belli, A., Sabbatini, L., & Pierleoni, P. (2022a). Recent Advances in Internet of Things Solutions for Early Warning Systems: A Review. Sensors, 22(6), 2124. https://doi.org/10.3390/s22062124 Fajri, A. H., Murti, M. A., & Priramadhi, R. A. (2021). Design of earthquake early warning system based OMRON D7S vibrate sensor. IOP Conference Series: Materials Science and Engineering, 1098(4), 042099. https://doi.org/10.1088/1757-899X/1098/4/042099 Fuady, M., Munadi, R., & Fuady, M. A. K. (2021). Disaster mitigation in Indonesia: Between plans and reality. IOP Conference Series: Materials Science and Engineering, 1087(1), 012011. https://doi.org/10.1088/1757-899X/1087/1/012011 Gupta, T., & Roy, S. (2024). Applications of Artificial Intelligence in Disaster Management. Proceedings of the 2024 10th International Conference on Computing and Artificial Intelligence, 313–318. https://doi.org/10.1145/3669754.3669802 Harahap, Partaonan, Benny Oktrialdi, and Rahmad Fauzi Siregar. 2023. “Implementasi Alat Pendeteksi Gempa Berbasis Arduino Uno Dengan Memanfaatkan Sensor Getar (Vibration).” Seminar Nasional Teknik Elektro. Howard, S. K., Schrum, L., Voogt, J., & Sligte, H. (2021). Designing research to inform sustainability and scalability of digital technology innovations. Educational Technology Research and Development, 69(4), 2309–2329. https://doi.org/10.1007/s11423-020-09913-y Ira, A. P., & Purwantara, S. (2021). School Community Preparedness in Anticipation of Earthquake and Tsunami Threats in Temon Sub-District. IOP Conference Series: Earth and Environmental Science, 884(1), 012046. https://doi.org/10.1088/1755-1315/884/1/012046 Köhli, M., Weimar, J., Schmidt, S., Schmidt, F. P., Lambertz, A., Weber, L., Kaminski, J., & Schmidt, U. (2024). Arduino-Based Readout Electronics for Nuclear and Particle Physics. Sensors, 24(9), 2935. https://doi.org/10.3390/s24092935 Komarizadehasl, S., Mobaraki, B., Ma, H., Lozano-Galant, J.-A., & Turmo, J. (2021). Development of a Low-Cost System for the Accurate Measurement of Structural Vibrations. Sensors, 21(18), 6191. https://doi.org/10.3390/s21186191 Laia, Firdaus, Tobias Duha, Mitranikasih Laia, Amirudin Khorul Huda, and Agung Jasuma. 2023. “Klasifikasi Data Gempa Bumi Di Pulau Sumatera Menggunakan Algoritma Naïve Bayes.” Jurnal Informatika 2(1):23–27. doi: 10.57094/ji.v2i1.840. Liu, T., Zhang, M., Li, Z., Dou, H., Zhang, W., Yang, J., Wu, P., Li, D., & Mu, X. (2025). Machine learning-assisted wearable sensing systems for speech recognition and interaction. Nature Communications, 16(1), 2363. https://doi.org/10.1038/s41467-025-57629-5 Mamahit, Calvin. 2024. “Rumah Pintar Dengan Lampu Kontrol Suara Menggunakan Arduino Uno R3.” Electrician : Jurnal Rekayasa Dan Teknologi Elektro 18(2):144–52. doi: 10.23960/elc.v18n2.2567. Mar’atuzzulfa, Salma, Rastri Prathivi, and Susanto. 2025. “Klasifikasi Gempa Bumi Berdasarkan Magnitudo Menggunakan Metode Logistic Regression.” KESATRIA: Jurnal Penerapan Sistem Informasi (Komputer & Manajemen) 6(1):227–34. Martin, K., and D. Susandi. 2022. “Perancangan Dan Implementasi Sistem Irigasi Kabut Otomatis Tanaman Edelweis Menggunakan Mikrokontroler Arduino Uno.” Jurnal IKRA-ITH INFORMATIKA 6(103):57–66. McBride, S. K., Smith, H., Morgoch, M., Sumy, D., Jenkins, M., Peek, L., Bostrom, A., Baldwin, D., Reddy, E., De Groot, R., Becker, J., Johnston, D., & Wood, M. (2022). Evidence-based guidelines for protective actions and earthquake early warning systems. GEOPHYSICS, 87(1), WA77–WA102. https://doi.org/10.1190/geo2021-0222.1 Nagasa, M. M., & Johnson, P. L. D. (2025). Industrial Internet of Things for a Wirelessly Controlled Water Distribution Network. Sensors, 25(8), 2348. https://doi.org/10.3390/s25082348 Patel, S. C., & Allen, R. M. (2022). The MyShake App: User Experience of Early Warning Delivery and Earthquake Shaking. Seismological Research Letters, 93(6), 3324–3336. https://doi.org/10.1785/0220220062 Ramdhan, M., Palgunadi, K. H., Mukti, M. M., Librian, V., Daniarsyad, G., Muttaqy, F., Hidayat, E., Syuhada, S., Hanif, M., Mursitantyo, A., Lühr, B.-G., Nugraha, A. D., Widiyantoro, S., Setyonegoro, W., & Febriani, F. (2025). Aftershock sequence of the Yogyakarta earthquake 2006 (Mw ~ 6.4), Indonesia, based on analysis of hypocenter relocation, static, and dynamic stress. Natural Hazards. https://doi.org/10.1007/s11069-025-07440-8 Romanssini, M., De Aguirre, P. C. C., Compassi-Severo, L., & Girardi, A. G. (2023). A Review on Vibration Monitoring Techniques for Predictive Maintenance of Rotating Machinery. Eng, 4(3), 1797–1817. https://doi.org/10.3390/eng4030102 Sekine, K., & Hayakawa, K. (2022). Development of Vibration Measurement System using a Microcontroller. EPI International Journal of Engineering, 5(2), 98–103. https://doi.org/10.25042/epi-ije.082022.04 Setiawan, B., Rizal, M., Yunita, H., Saidi, T., Hasan, M., & Zulkifli, Z. (2022). Validating a low-cost seismometer using a shaking table. E3S Web of Conferences, 340, 02009. https://doi.org/10.1051/e3sconf/202234002009 Silalahi, Andri, Deddy Hartama, Ika Okta Kirana, Indra Gunawan, and Sumarno Sumarno. 2022. “Rancang Bangun Alat Pendeteksi Kebocoran Pada Tabung Gas Menggunakan Arduino Berbasis Sms.” Jurnal Krisnadana 1(3):48–58. doi: 10.58982/krisnadana.v1i3.178. Simanjuntak, T., & Ririmasse, M. (2021). Archaeology of disaster in Indonesia: Where are we now? Berita Sedimentologi, 47(3), 17–21. https://doi.org/10.51835/bsed.2021.47.3.351 Sinaga, G. H. D., Loeqman, A., Siagian, R. C., & Sinaga, M. P. (2022). Analysis of Coulomb Stress Changes in Aceh Earthquake on Sibayak Volcano. Jurnal Pendidikan Fisika Dan Teknologi, 8(2), 217–227. https://doi.org/10.29303/jpft.v8i2.4409 Tansa, Salmawaty, Nur’aeni Latekeng, Raghel Yunginger, and Iskandar Z. Nasibu. 2024. “Monitoring Kualitas Air Sungai (Kekeruhan, Suhu, TDS,PH) Menggunakan Mikrokontroler Atmega328.” Jambura Journal of Electrical and Electronics Engineering 6(1):70–75. doi: 10.37905/jjeee.v6i1.23315. Tian, B., Liu, W., Mo, H., Li, W., Wang, Y., & Adhikari, B. R. (2023). Detecting the Unseen: Understanding the Mechanisms and Working Principles of Earthquake Sensors. Sensors, 23(11), 5335. https://doi.org/10.3390/s23115335 Witjaksana, Budi, and Andi Syaiful Amal. 2021. “Penerapan Sensor Pedeteksi Dini Gempa Bumi Pada Bangunan Konstruksi.” Seminar Keinsinyuran Program Studi Program Profesi Insinyur 1(1):26–32. doi: 10.22219/skpsppi.v1i0.4216. Zhukovsky, V., Rusu, I., Zavoloka, M., & Grynyova, I. (2021). The concept of an automatic system for preliminary entry of hazardous facility into emergency mode with an approaching earthquake. IOP Conference Series: Materials Science and Engineering, 1141(1), 012023. https://doi.org/10.1088/1757-899X/1141/1/012023